Nietzsche and his early Theoretical Critique to Schopenhauer’s philosophy - Ramírez Jaramillo, John Fredy (Estudios de Filosofía, 2009)
Between October 1867 and April 1868 Nietzsche writes a long note where he states a whole series of important objections to Schopenhauer’s philosophical system. These notes enjoy a significant importance due to the fact that, when approached from a wide perspective, they show the preoccupation that the young philosopher has to clarify at this early stage the conceptual horizon from which he takes his bearings; at the same time, from a more specific point of view, those notes enable us to follow up some of the initial elements that will motivate his further radical critique to Schopenhauer’s philosophy. This essay analyzes the different questions formulated by Nietzsche about the standardization of Will as a Thing-in-itself and the argumentation with which is defined its transition towards the representation level.